Qualifications for selecting a coach for administrative and technical sports performances from the point of view of specialists in Syria (Journal of Hama University, 2022)
This study aims to identify the basic components of the sports shows and to determine the most important component.The descriptive method is used with a questionnaire includes 13 of the sports show component. The questionnaire distributed on the sample of the study which includes 20 sports show's specialists.The study concludes that the important components are: music, costumes, performance, formations, time and the space of the show. The study also determines that some department should be focus on, to improve sport shows and the trainers in this section.
Keywords: sports shows, the components of the sports shows.